1996
DOI: 10.1007/bf01795242
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the posterior tibial artery: implications for free transplants of the fibula

Abstract: A well-documented case of absence of the posterior tibial a. is reported. We have studied 40 personal case-records of dissection of the arteries of the leg in fresh corpses. This study allowed classification of the origins of the leg arteries from the popliteal a. into 7 groups. Several findings emerged: 1) the peroneal a. is constant, for phylogenetic and embryologic reasons, 2) the posterior tibial a. is absent in 1 to 5% of cases [1, 2, 4, 6-8] (Fig. 4), in which case the vascularisation of the fibula remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 4 publications
(2 reference statements)
0
14
0
1
Order By: Relevance
“…Seven cadaveric and 19 clinical radiographic studies were found eligible for inclusion, with average sample size of 113 and 263 limbs, respectively (Table ). Conventional dissection was performed in all the cadaveric studies, and was supplemented with postmortem angiography in one study . In the radiographic studies, catheter arteriography (CA) was the commonest modality used in 12 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven cadaveric and 19 clinical radiographic studies were found eligible for inclusion, with average sample size of 113 and 263 limbs, respectively (Table ). Conventional dissection was performed in all the cadaveric studies, and was supplemented with postmortem angiography in one study . In the radiographic studies, catheter arteriography (CA) was the commonest modality used in 12 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional dissection was performed in all the cadaveric studies, and was supplemented with postmortem angiography in one study. 30 In the radiographic studies, catheter arteriography (CA) was the commonest modality used in 12 studies. Magnetic resonance angiography (MRA) and multidetector row computed tomographic angiography (MDCTA) were used in four and three studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Once it has been visualized that the posterior tibialis artery is present, harvest of the fibula flap may proceed without any concern for devascularizing the leg. 21,22 It should be noted that with the anterior approach for this procedure, visualization of the tibioperoneal trunk occurs after performing the osteotomies and dissecting the whole length of the pedicle. Thus, aborting the procedure due to diagnosis of peroneum magnum via the anterior approach is far more morbid than with the posterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…The vascularization of fibula remains normal even in the absence of PT since the nutrient artery to fibula is provided by the PR. 10 But harvesting of the peroneal artery in vascularized fibular grafting 19 would be contraindicated in rare type III infrapopliteal patterns, particularly when the PR is the only artery to supply the foot. It may be necessary to modify the angioplasty technique to take account of the absence of vessels in order to minimize risk of complications.…”
Section: -18mentioning
confidence: 99%
“…[3][4][5] The incidence of hypoplastic-aplastic PT ranges between 0.8-3.8% in the angiographic studies whereas in the anatomical studies it ranges between 1.5-11%. [1][2][3][6][7][8][9][10] Compensatory hypertrophy of the PR with a hypoplastic or aplastic PT or AT may indicate variant arterial supply to the foot. 1 This enlarged PR, the "peronea magna" or "great" peroneal artery as described by Senior, either joins and reinforces the PT or replaces it in the distal leg and foot.…”
Section: Introductionmentioning
confidence: 99%